THE MANAGEMENT OF CULTURAL EVENTS AND TOURISM ATTRACTIONS IN THE INDONESIAN TOURISM VILLAGES - Elwisam; Tri Waluyo; Kumba Digdowiseiso; Nguyen Duc Tri; Jassmin Johari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The exploration of tourist villages holds significant importance in endeavors to foster sustainable tourism in Indonesia. Tourist villages not only provide aesthetic appeal, cultural distinctiveness, and indigenous knowledge, but also have a beneficial impact on the economic and social advancement of local communities. The objective of this study is to examine the design and implementation of cultural event management in Indonesian tourist villages, with the aim of enhancing tourist attraction. Additionally, the study seeks to assess the impact of cultural event management on tourist experiences and identify the key factors that contribute to the success of such management in increasing tourist attraction in tourist villages. This text discusses the role of local communities in promoting the sustainability of these activities. Qualitative methods offer a comprehensive framework for investigating the intricacies and subtleties of cultural activities and their influence on tourist attractions in tourist villages. Within this framework, qualitative methods encompass various approaches, including literature reviews, participant observation, and content analysis. The findings of the study indicate that the effectiveness of cultural events in Indonesian tourist villages is not solely determined by their level of interest, but also by their capacity to foster cultural sustainability, engage local communities, and showcase the distinctiveness of the destination.